THE QUESTIONNAIRE ANALYSIS OF STUDENTS NEEDS TO MODULE OF ISLAMIC RELIGION EDUCATION PROGRAM WITH ANTI-RADICALISM AND ANTI-TERRORISM - Syahrizal Syahrizal; Liza Yulia Sari; Febrina Riska Putri (Universitas Pendidikan Ganesha, 2017)
The purpose of this study is to determine students’ needs to the module of Islamic education courses that have principles of anti-radicalism and anti-terrorism. This research is a developmental research. The models and procedures of this research use 4-D (four-D models) development model that consist of four stages: define, design, develop, and disseminate. The data analysis technique used in this research is descriptive analysis describing the result of the module of Islamic education course that has anti-radicalism and anti-terrorism, which has been designed containing the identity of the course, instruction of the use of module for students and lecturers, worksheet for students, answer keys to the work sheet, evaluation sheets, and keys for the evaluation sheets.